Understanding the Effect of Ionic Liquids as Adjuvants in the Partition of Biomolecules in Aqueous Two-Phase Systems Formed by Polymers and Weak Salting-Out Agents - Neves, Catarina M. S. S. (Biochem Eng J, 2019)
Ionic liquids (ILs) as adjuvants in polymer-salt aqueous two-phase systems (ATPS) have been used to improve the extraction of biomolecules. However, the impact of ILs as adjuvants on the partition of biomolecules is still poorly understood. Previous works mostly focused on ATPS based on strong salting-out agents, which may mask the IL effect. In this work, ATPS formed by polyethylene glycol (PEG 400) and a weak salting-out salt ((NH(4))(2)SO(4)) with a wide number of ILs as adjuvants (chloride-based combined with cholinium, imidazolium, pyrrolidinium, piperidinium, tetralkylammonium and tetralkylphosphonium cations) were investigated. The respective phase diagrams were determined, and the systems extraction performance for a wide range of biomolecules (phenolic compounds, alkaloids and amino acids) was investigated. The results obtained show that ILs as adjuvants in polymer-salt ATPS modulate the partition of biomolecules. In particular, more hydrophobic ILs significantly enhance the partition of more hydrophobic biomolecules to the PEG-rich phase (where the IL is enriched). Furthermore, the intensity of the IL effect is more pronounced when using weak salting-out agents. A linear correlation between the biomolecules and the ILs partition coefficients, and with the biomolecules octanol-water partition coefficients, was found. In most ATPS formed by polymers and salts using ILs as adjuvants, the biomolecules partition is driven by the ILs partition and by the difference in hydrophobicity between the coexisting phases.